BSM-MBR: A Benchmark Simulation Model to Compare Control and Operational Strategies for Membrane Bioreactors - Maere, Thomas; Verrecht, Bart; Moerenhout, Stefanie; Judd, Simon J.; Nopens, Ingmar (Elsevier Science B.V., Amsterdam., 2011)
A benchmark simulation model for membrane bioreactors (BSM-MBR) was developed to evaluate operational and control strategies in terms of effluent quality and operational costs. The configuration of the existing BSM1 for conventional wastewater treatment plants was adapted using reactor volumes, pumped sludge flows and membrane filtration for the water-sludge separation. The BSM1 performance criteria were extended for an MBR taking into account additional pumping requirements for permeate production and aeration requirements for membrane fouling prevention. To incorporate the effects of elevated sludge concentrations on aeration efficiency and costs a dedicated aeration model was adopted. Steady-state and dynamic simulations revealed BSM-MBR, as expected, to out-perform BSM1 for effluent quality, mainly due to complete retention of solids and improved ammonium removal from extensive aeration combined with higher biomass levels. However, this was at the expense of significantly higher operational costs. A comparison with three large-scale MBRs showed BSM-MBR energy costs to be realistic. The membrane aeration costs for the open loop simulations were rather high, attributed to non-optimization of BSM-MBR. As proof of concept two closed loop simulations were run to demonstrate the usefulness of BSM-MBR for identifying control strategies to lower operational costs without compromising effluent quality.